How Deep Can Surface Signals Be Traced in the Critical Zone? Merging Biodiversity with Biogeochemistry Research in a Central German Muschelkalk Landscape - Küsel, Kirsten; Totsche, Kai U.; Trumbore, Susan E.; Lehmann, Robert; Steinhäuser, Christine; Herrmann, Martina (Frontiers in Earth Science, 2016)
The Earth’s Critical Zone (CZ) is a thin living layer connecting atmosphere and geosphere, including aquifers. Humans live in the CZ and benefit from the vital supporting services it provides. However, the CZ is increasingly impacted by human activities including land and resource use, pollution and climate change. Recent interest in uniting the many disciplines studying this complex domain has initiated an international network of research infrastructure platforms that allow access to the CZ in a range of geologic settings. In this paper a new such infrastructure platform associated with the Collaborative Research Center AquaDiva is described, that uniquely seeks to combine CZ research with detailed investigation of the functional biodiversity of the subsurface. Overall, AquaDiva aims to test hypotheses about how water connects surface conditions set by land cover and land management to the biota and biogeochemical functions in the subsurface. With long-term and continuous observations, hypotheses about how seasonal variations and extreme events at the surface impact subsurface processes, community structure and function, are tested. AquaDiva has established the Hainich Critical Zone Exploratory (CZE) in central Germany in an alkaline geological setting of German Triassic Muschelkalk formations. The Hainich CZE includes specialized monitoring wells to access the vadose zone and two main groundwater complexes in limestone and marlstone parent materials along a ~6 km transect spanning forest, pasture and agricultural land uses. Initial results demonstrate fundamental differences in the biota and biogeochemistry of the two aquifer complexes that trace back to the land uses in their respective recharge areas. They also show the importance of antecedent conditions on the impact of precipitation events on responses in terms of groundwater dynamics, chemistry and ecology. Thus we find signals of surface land use and events can be detected in the subsurface CZ. Future research will expand to a second CZE in contrasting siliciclastic parent rock, to evaluate the relative importance of parent material lithology versus surface conditions for the emergent characteristics of the subsurface CZ and biodiversity. The Hainich CZE is open to researchers who bring new questions that the research platform can help answer.